2020
DOI: 10.1108/arj-11-2018-0204
|View full text |Cite
|
Sign up to set email alerts
|

Earnings management prior to private debt issuance

Abstract: Purpose The purpose of this paper is to evaluate the extent to which firms manage earnings prior to private debt issuance. Design/methodology/approach This is an empirical archival research paper using financial statement data and data related to private debt issuance. Findings The results indicate that, on average, firms engage in income-increasing earnings management in the period prior to a new private debt issuance. In addition, it was found that this income-increasing earnings management is limited to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 47 publications
(67 reference statements)
0
14
0
Order By: Relevance
“…Since Burgstahler and Dichev (1997) and Degeorge et al. (1999) identify three behavioral earnings benchmarks—avoid losses, avoid earnings declines and avoid missing analysts’ forecasts, a large volume of prior research provides substantial evidence that firms use accounting discretion to achieve earnings benchmarks (An et al., 2014; Ater & Hansen, 2020; Barua et al., 2010; Burgstahler & Eames, 2006; Cazier et al., 2015; Cohen et al., 2011; Fan et al., 2010; Lee, 2014; Matsumoto, 2002; McVay, 2006; Moehrle, 2002; Nagar & Sen, 2017).…”
Section: Relation To Prior Research and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Burgstahler and Dichev (1997) and Degeorge et al. (1999) identify three behavioral earnings benchmarks—avoid losses, avoid earnings declines and avoid missing analysts’ forecasts, a large volume of prior research provides substantial evidence that firms use accounting discretion to achieve earnings benchmarks (An et al., 2014; Ater & Hansen, 2020; Barua et al., 2010; Burgstahler & Eames, 2006; Cazier et al., 2015; Cohen et al., 2011; Fan et al., 2010; Lee, 2014; Matsumoto, 2002; McVay, 2006; Moehrle, 2002; Nagar & Sen, 2017).…”
Section: Relation To Prior Research and Hypothesis Developmentmentioning
confidence: 99%
“…Since Burgstahler and Dichev (1997) and Degeorge et al (1999) identify three behavioral earnings benchmarks-avoid losses, avoid earnings declines and avoid missing analysts' forecasts, a large volume of prior research provides substantial evidence that firms use accounting discretion to achieve earnings benchmarks Ater & Hansen, 2020;Barua et al, 2010;Burgstahler & Eames, 2006;Cazier et al, 2015;Cohen et al, 2011;Fan et al, 2010;Lee, 2014;Matsumoto, 2002;McVay, 2006;Moehrle, 2002;Nagar & Sen, 2017). Moreover, prior studies also provide substantial evidence of real activity management to achieve earnings benchmarks, mainly focusing on operating activities (Baber et al 1991;Bushee, 1998;Dechow & Sloan, 1991;Roychowdhury, 2006), and investing activities (Barth et al, 1990;Bartov, 1993;Beatty et al, 1995;Beatty & Harris, 1999;Collins et al, 1995;Dechow & Shakespeare, 2009;Jordan et al, 1998;Lifschutz, 2002;Scholes et al, 1990).…”
Section: Prior Researchmentioning
confidence: 99%
“…Al-Okaily et al (2020) find that earnings management is not significant in family businesses, while also investigating the higher predisposition for earnings management in enterprises with a financial connection. Ater and Hansen (2020) assess the range of business earnings manipulation strategies prior to private debt issuance. El Diri et al (2020) detect the discrepancies among markets of high and low concentration in applying accrual and real earnings management.…”
Section: Combined Model Of Earnings Managementmentioning
confidence: 99%
“…Previous studies have found various conditions that cause companies to undertake EM more intensively. Among them is the need for external funds (Zhang et al , 2020; Ater and Hansen, 2020; Alhadab, 2018; Liu et al , 2010). Ater and Hansen (2020) and Liu et al (2010) found that listed companies increase reported earnings ahead of debt issuance.…”
Section: Introductionmentioning
confidence: 99%
“…Among them is the need for external funds (Zhang et al , 2020; Ater and Hansen, 2020; Alhadab, 2018; Liu et al , 2010). Ater and Hansen (2020) and Liu et al (2010) found that listed companies increase reported earnings ahead of debt issuance. Alhadab (2018) proved that companies conduct EM around the initial public offering of equity.…”
Section: Introductionmentioning
confidence: 99%